Metodologia da ilustração científica : divulgação da Entomologia forense ao grande público - Soalheiro, Ana Calheiros, 1990- (2015)
The work here presented addresses the several steps in the construction of a concise brochure concerning Forensic Entomology, after a noticeable lack of publications in this field. The structure of this dissertation details extensively the several phases of scientific illustration, which begins with a deep understanding of the species meant to be represented. The scientific part of this dissertation clarifies the basic concepts of entomology, while providing a general context of insect biology. Concepts such as taxonomy, anatomy, ecology and metamorphosis are explained in a way which allows the understanding of the theory and practice of forensic entomology. In this field, it is important to highlight the interaction of necrophagous insects with the dead body’s stages of decomposition, as well as the crucial role of these animals when calculating the Post-Mortem Interval (PMI) and the consequences this has in everyday life. The final brochure focuses essentially on the necrophagous species Calliphora Vicina and Lucilia Sericata both from the Calliphoridae family as well as the Sarcophagidae family in general, serving as examples of the most common species of Diptera responsible for accelerating vertebrates’ decomposition. An historical and evolutionary context on scientific illustration is also provided, highlighting some important authors and technological advances that have contributed to the evolution of this strain of drawing. This part depicts the task of the illustrator when researching other drawings made about the same subject as a way to identify and avoid inaccuracies and also to improve his illustration. This method of illustration is aimed at the materialization of the brochure and clarifies the several stages of the illustrator’s work. It begins with the collection and conservation of the species, which leads to laboratorial observation and finally culminating in studio production, from the preliminary drawing to the final artwork